On the Laser Micro Cutting: Experimentation and Mathematical Modeling based on RSM-CCD (Journal of Engineering, 2023)
The laser micro-cutting process is the most widely commonly applied machining process which can be applied to practically all metallic and non-metallic materials. While this had challenges in cutting quality criteria such as geometrical precision, surface quality and numerous others. This article investigates the laser micro-cutting of PEEK composite material using nano-fiber laser, due to their significant importunity and efficiency of laser in various manufacturing processes. Design of experiential tool based on Response Surface Methodology (RSM)-Central Composite Design (CCD) used to generate the statistical model. This method was employed to analysis the influence of parameters including laser speed, laser power, laser frequency and number of passes on the cutting characteristics -and geometrical. Cutting-geometry requirements are significant quality features since they are one of the metrics for the geometrical precision of micro-cutting proses it was concluded that higher laser power, slower speed, and more pass number result in a low kerf taper, these parameters have a significant impact on the other cutting characteristics, and geometrical. Whereas the frequency has the lowers impact on the cutting geometrical. Finally, the experiments show Maximum depth was 2000, width minimum top kerf width was 305.56 µm and the minimum angle of 2.8906.